Mobile Computing, Applications, and Services First International ICST Conference, MobiCASE 2009, San Diego, CA, USA, October 26-29, 2009, Revised Selected Papers - Zerfos, Petros; Montanari, Rebecca; Phan, Thomas (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2010)
This proceedings volume includes the full research papers presented at the First Int- national Conference on Mobile Computing, Applications, and Services (MobiCASE) held in San Diego, California, during October 26-29, 2009. It was sponsored by ICST and held in conjunction with the First Workshop on Innovative Mobile User Inter- tivity (WIMUI). MobiCASE highlights state-of-the-art academic and industry research work in - main topics above the OSI transport layer with an emphasis on complete end-to-end systems and their components. Its vision is largely influenced by what we see in the consumer space today: high-end mobile phones, high-bandwidth wireless networks, novel consumer and enterprise mobile applications, scalable software infrastructures, and of course an increasingly larger user base that is moving towards an almost a- mobile lifestyle. This year's program spanned a wide range of research that explored new features, algorithms, and infrastructure related to mobile platforms. We received submissions from many countries around the world with a high number from Europe and Asia in addition to the many from North America. Each paper received at least three in- pendent reviews from our Technical Program Committee members during the Spring of 2009, with final results coming out in July. As a result of the review process, we selected 15 high-quality papers and complemented them with six invited submissions from leading researchers, reaching the final count of 21 papers in the program.